As doenças crônicas não transmissíveis: uma análise entre técnicos administrativos da odontologia em Uberlândia/MG - Rodrigues, Mayrines Aparecida da Silva (2017)
Chronic Noncommunicable Diseases (CNCDs) have been causing significant impacts on the Brazilian health system, increasing expenses in the Brazilian health system due to absenteeism at work, early retirements and death of the economically active population. The causes are related to the lifestyle chosen by the subjects to live, work and die, and can be avoided through preventive actions. Thus, this descriptive study, with a qualitative and quantitative approach, was carried out among Administrative Technicians of Dentistry of the Federal University of Uberlândia (UFU). It aimed to identify the CNCDs that affect the workers and specifically to identify the risk profile for the development of these diseases, to evaluate workers' knowledge about their health and the presence of diseases, and to participate in health promotion activities or programs. The last results of the studies of the Ministry of Health and study of authors such as Lacaz, Rouquayrol, Mendes and others on CNCD, Worker's Health and the health-illness process at work were used as reference. The sample consisted of 98 workers from two UFU units. The instrument used to collect data was a questionnaire composed of semi structured questions, respecting the inclusion and exclusion criteria, of which 72.22% were female and 27.78% were male. The predominant age range was 50-59 years for both genders. he predominant level of education was the complete upper level. The positions with the largest number of workers were administrative assistant, nursing assistant, dental surgeons and secretaries. Regarding health status 55.55% considered good, 42.22% optimum and 2.22% bad. It was identified that 47.69% of workers have Systemic Arterial Hypertension and in 10% of them they have at least one more associated chronic disease such as tendonitis, asthma, arthrosis and glaucoma. Regarding lifestyle, 84.44% are non-smokers and 5.56% are smokers and consume up to 25 cigarettes per day, 48.89% of both genders consume alcoholic beverages, 54% consume little salt, and consumption of fruits, Vegetables and vegetables 86.67% have a habit of consuming and still, 58.89% practice physical activity. Regarding work processes, 64% do not feel tired after work and 56% do not feel irritated during work. he workers of the units where the research took place know the health risks, but do not participate in preventive health promotion programs offered by the institution, being thus exposed to the risk factors for the development of CNCDs, since they are diseases of slow development and Lifelong learning. Finally, the study serves as a source of research to guide new paths to travel in the promotion of health and prevention of diseases of CNCDs. It is also hoped that actions and interventions will be directed not only to the workers of the units studied, but to all the workers of the institution.